Fungi associated to pollution sources in Mandinga Lagoon, Veracruz, Mexico and their bioactive potential - Lagunes, Irene (2026)
Introduction: The Mandinga Lagoon System, located in the state of Veracruz, Mexico, is under significant demographic pressure due to urban expansion around the municipalities of Boca del Río, Medellín and Alvarado. Aquatic fungi are known to respond to pollution, maintaining and adapting their life cycles to obtain their carbon source by decomposing organic matter. Objectives: To isolate and identify fungi from sampling sites associated with punctual sources of contamination and explore their antiproliferative activity against solid tumor cell lines. Methods: Two liters of water were collected in four sampling sites. The isolation of filamentous fungi was made on Potato Dextrose Agar by plate streaking method. Monosporic isolates were identified using taxonomic keys, and molecular identification was made using the primers ITS1F/ITS4. Fungal extracts were obtained from biomass in culture medium, and their antiproliferative activity was evaluated against two human solid tumor cell lines. Results: Seven fungal strains belonging to five different genera of Ascomycetes were isolated: Neopestalotiopsis, Cladosporium, Fusarium, Purpureocillium and Penicillium. Hexane and chloroform broth-extracts from Purpureocillium lavendulum showed the highest activity against A549 and HeLa cell lines (GI50 = 3 μg/ml and GI50 = 12 μg/ml, respectively). Meanwhile, the chloroform biomass-extract from Penicillium sp. and ethyl acetate broth-extract from Fusarium oxysporum showed GI50 values < 50 μg/ml. Conclusions: The ability of fungi to produce secondary metabolites as response to environmental stress represents an opportunity to perform bioprospecting studies. The results in this study indicate that P. lavendulum is a promising fungus to continue the bioguided separation of bioactive compounds with antiproliferative activity.